Cigarette Smoking History and Functional Outcomes After Spontaneous Intracerebral Hemorrhage. Issue 3 (March 2019) - Chen, Ching-Jen; Ding, Dale; Ironside, Natasha; Buell, Thomas J.; Southerland, Andrew M.; Koch, Sebastian; Flaherty, Matthew; Woo, Daniel; Worrall, Bradford B.
Abstract : Background and Purpose—: Although cigarette use may be a risk for intracerebral hemorrhage (ICH), animal models suggest that nicotine has a potential neuroprotective effect. The aim of this multicenter study is to determine the effect of smoking history on outcome in ICH patients. Methods—: We analyzed prospectively collected data from the Ethnic/Racial Variations of Intracerebral Hemorrhage study and included patients with smoking status data in the analysis. Patients were dichotomized into nonsmokers versus ever-smokers, and the latter group was further categorized as former (>30 days before ICH) or current (⩽30 days before ICH) smokers. The primary outcome was 90-day modified Rankin Scale score shift analysis. Secondary outcomes were in-hospital mortality and mortality, Barthel Index, and self-reported health status measures at 90 days. Results—: The overall study cohort comprised 1509 nonsmokers and 1423 ever-smokers (841 former, 577 current, 5 unknown). No difference in primary outcome was observed between nonsmokers versus ever-smokers (adjusted odds ratio [aOR], 1.041; 95% CI, 0.904–1.199; P =0.577). No differences in primary outcome were observed between former (aOR, 0.932; 95% CI, 0.791–1.178; P =0.399) or current smokers (aOR, 1.178; 95% CI, 0.970–1.431; P =0.098) versus nonsmokers. Subgroup analyses by race/ethnicity demonstrated no differences in primary outcome when former and current smokers were compared with nonsmokers. Former, but not current, smokers had a lower in-hospital mortality rate (aOR, 0.695; 95% CI, 0.500–0.968; P =0.031), which was only observed in Hispanics (aOR, 0.533; 95% CI, 0.309–0.921; P =0.024). Differences in self-reported health status measures were only observed in whites. Conclusions—: Cigarette smoking history does not seem to provide a beneficial effect on 90-day functional outcome in patients with ICH. Abstract : Supplemental Digital Content is available in the text.